ANALISIS POTENSI, KONTRIBUSI, DAN EFEKTIVITAS PAJAK KENDARAAN BERMOTOR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PEMERINTAH PROVINSI SULAWESI SELATAN - Hartati, Hartati; Su’un, Muh.; Junaid, Asriani (COMPETITIVENESS, 2019)
The objectives of this study are: 1) to determine and analyze the potential of Motor Vehicle Taxes in increasing South Sulawesi Province Original Revenue, 2) to determine and analyze the contribution of Motor Vehicle taxes in increasing Regional Original Income in South Sulawesi Province, and 3) to determine and analyzing the effectiveness of Motor Vehicle taxes in increasing the Regional Original Revenue of South Sulawesi Province.This study uses secondary data in the form of: 1) data on the number of motorized vehicles in South Sulawesi Province in 2014-2018, 2) data on targets and realization of Motor Vehicle Taxes for 2014-2018, and 3) data on targets and realization of Regional Original Revenue in 2014 -2018. Data collection was carried out at the Regional Revenue Agency Office of South Sulawesi Province, using the formula for potential, contribution, and effectiveness.The results showed that: 1) Motor Vehicle Taxes have enormous potential in supporting the Regional Original Income of South Sulawesi Province but have not been optimal in withdrawing and management, 2) Motor Vehicle Taxes have a significant contribution to support the Regional Original Income of South Sulawesi Province, and 3) Motor Vehicle Tax is effective in supporting the increase in Regional Original Revenue in South Sulawesi Province. This means that the Motor Vehicle Tax has a very significant effect in increasing the Regional Original Revenue of South Sulawesi Province. Keywords: Potential, Contribution, Effectiveness, Motor Vehicle Taxes, Regional Original Income